Bahasa sebagai Jejaring Budaya Asia Tenggara - Agus Suwignyo (Jurnal Sejarah Citra Lekha, 2021)
The connection of Southeast Asian region was a result of migration and trade. While this holds true according to the mainstream studies, there has been a growing scholarly attention paid to the role of languages. Languages significantly shaped the roots of cultural identity of the region. The aim of this paper is to examine languages as an objective factor in the construction of Southeast Asian cultural connection. This paper argues that the linguistic roots of Southeast Asia created shared elements of cultural identities by which Southeast Asian nations had developed. In the nineteenth and twentieth century, the shared elements moved into different trajectories of identities especially as they were fostered by the formation of colonial and post-colonial states. Although today the nations of Southeast Asia speak of their own “national language”, the same language elements remain to exist. This shows a strong sense of shared elements on which the cultural network of Southeast Asian region was based.